2008
DOI: 10.1128/cvi.00381-07
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Responses of Type 1 Diabetes Patients to Mycobacterium avium subsp. paratuberculosis Lend Support to the Infectious Trigger Hypothesis

Abstract: Mycobacterium avium subsp. paratuberculosis is a zoonotic pathogen whose association with Crohn's disease in humans is under scrutiny. The objective of this work was to investigate its association with other chronic diseases such as type 1 diabetes mellitus (T1DM), where the involvement of a persistent pathogen such as M. avium subsp. paratuberculosis could be the trigger. For this purpose, 59 diabetic patients and 59 healthy controls were investigated for the presence of antibodies against two recombinant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 24 publications
4
76
1
1
Order By: Relevance
“…However, recent advancements in MAP research indicated the presence and role of MAP in patients with various diseases such as Type-1 Diabetes (Sechi et al, 2008), autoimmune thyroiditis (D"Amore et al, 2010), multiple sclerosis (Cossu et al, 2013a), autism (Dow, 2011), sarcoidosis (EL-Zaatari et al, 1996) and autoimmune arthritis (Moudgil et al, 1997). Our study correlates with the finding of some authors that have claimed the association of MAP infection with autoimmune disorder viz.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, recent advancements in MAP research indicated the presence and role of MAP in patients with various diseases such as Type-1 Diabetes (Sechi et al, 2008), autoimmune thyroiditis (D"Amore et al, 2010), multiple sclerosis (Cossu et al, 2013a), autism (Dow, 2011), sarcoidosis (EL-Zaatari et al, 1996) and autoimmune arthritis (Moudgil et al, 1997). Our study correlates with the finding of some authors that have claimed the association of MAP infection with autoimmune disorder viz.…”
Section: Discussionsupporting
confidence: 89%
“…MAP has also been associated with Type-1 Diabetes (Sechi et al, 2008), autoimmune thyroiditis (D"Amore et al, 2010), multiple sclerosis (Cosu et al, 2013a), autism (Dow, 2011), sarcoidosis (EL-Zaatari et al, 1996), rheumatoid arthritis (Moudgil et al, 1997), autoimmune hepatitis (Miyata et al, 1995), primary biliary cirrhosis (Vilagut et al, 1997), scleroderma (Danieli et al, 1992), Kawasaki disease (Yokota et al, 1993), Behcet"s disease (Direskeneli and Saruhan-Direskeneli, 2003) and Takayasu"s arteritis (Aggarwal et al, 1996). Information Vir Singh et al 21 on the association of MAP with different human health problems is yet to be recognized and taken seriously by the medical doctors and scientists in India.…”
Section: Introductionmentioning
confidence: 99%
“…The approximate economic loss due to paratuberculosis per sheep/farmer/year is around Rs 1,840 (US$ 38.33) in India (Vinodhkumar et al, 2013). There are evidences to relate MAP with human diseases like Crohn's disease (Greenstein, 2003) and type I diabetes (Naser et al, 2013, Sechi et al, 2008. As MAP is not killed by pasteurization , milk is considered as vehicle of transmission of MAP to humans.…”
Section: Introductionmentioning
confidence: 99%
“…C. pneumoniae establishes a latent infection in some cell types, with life-long persistence of the bacteria in the infected body, participating in the formation of atherosclerotic plaques and potentiating the inflammatory reaction at the site of infection (Roubalová et al, 2007). It can establish persistent infection in macrophages, associated with an alteration of their function, and can modulate the host immune response (Roubalová et al, 2007;Bulut et al, 2002); these immune cell populations are probably the deterrent to some autoimmune diseases such as T1DM (insulin-dependent) (Sechi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%